QUALIIT WORK-LIFE AND OCCUPATlONAL MENTAL HEALTH INTEGRATED MODEL: MODEL AND MODEL'S SCALES VALIDITY - Duro Martín, Antonio (Cuadernos de Administración, 2008)
This study's propose is to test the validity ofworklife and occupational health model 's measurement scales. This model includes four groups of structural conditions: work conditions, adaptation conditions, matching work-worker conditions, and subjective experience conditions (occupational well-being and health); and one group of modulating conditions. Using a 719 workers sample, and a cross-sectional design, we tested the significance ofthe explained variance ofthe occupational well-being and work-related mental ill-health scales by means of the resting model's scales . ResuIts support that the measurement scales of the work conditions, adaptation conditions, matching work-worker conditions, and modulating conditions explain significantly the workers' occupational well-being and health. It is concluded that the model is useful for a primary psychosocial risks evaluation in companies.